How do you simplify #(3x^ 2a - 4y az ^3a) ^2 #?

1 Answer
Jul 15, 2017

Answer:

#(3ax^2-4a^2yz^3)^2=9a^2x^4-24a^3x^2yz^3+16a^4y^2z^6#

Explanation:

First simplify how the expression is written:

#(3x^2a-4yaz^3a)^2# is better written as #(3ax^2-4a^2yz^3)^2#

We write pronumerals in alphabetical order and collect them together.

Now use the FOIL (firsts, outers, inners, lasts) to multiply:

#(3ax^2-4a^2yz^3) = (3ax^2-4a^2yz^3)(3ax^2-4a^2yz^3)#
#=9a^2x^4-12a^3x^2yz^3-12a^3x^2yz^3+16a^4y^2z^6#
#=9a^2x^4-24a^3x^2yz^3+16a^4y^2z^6#